AL-QADR DALAM ALQURAN: Analisis Tematik terhadap Sejumlah Lafal al-Qadr dalam Alquran - Mathar, M. Saleh (Hunafa: Jurnal Studia Islamika, 2010)
This article deals with the term al-qadr in the Qur’an. The things to discuss in this article are the essence of al-qadr, its process and its purpose. In discussing this term, the analytical-thematic method will be used to search the meanings of the term al-qadr in the Qur’an. Based on the result of analysis, it was found that al-qadr was the sunnat Allah itself which had been decided by God.  Then, it was  sunnat Allâh called natural law, or causality. The process of al-qadr began with the creation of the universe then the Creator (God) decided the natural law (sunnat Allâh) over it. One of the purposes of al-qadr is to  keep the order of His creation and the equilibrium among creatures in the universe.Kata Kunci: al-qadr, Alquran, sunnatullah, hukum alam